Assistance in the Development of Nutrient Water Cooling Technology for Hydroponic Farmers - Annisa Syafitri Kurniasetiawati; Bowo Yuli Prasetyo; Parisya Premiera Rosulindo; Windy Hermawan Mitrakusuma; Apip Badarudin; Muhammad Akmal; Rizki Muliawan (Jurnal Difusi, 2026)
The Indonesian hydroponic industry is expanding rapidly as awareness of food security grows. The JTRA-POLBAN Community Service Team mentored Ndaru Farm MSME in Batujajar Village, focusing on aquaponics. Greenhouse nutrient water temperatures can reach 38°C, exceeding the ideal 20–23°C and affecting harvests. Therefore, a water chiller-based cooling system was developed and tested on hydroponic tables. System performance was monitored through electricity consumption, temperature stability, and the growth of lettuce (Lactuca sativa) and bok choy (Brassica rapa). Growth parameters included weekly plant height and final harvest weight, compared with a control without cooling. Results showed that cooling maintained stable temperatures of 20–22°C, while without cooling they fluctuated at 28–29°C. Cooling increased lettuce height but reduced its mass, whereas bok choy experienced significant mass gain. Energy analysis confirmed cooling technology is more profitable for sustainable bok choy cultivation.